An Overview on Guillain Barre Syndrome - Gantala, Alekhya Reddy; Gangadhara, Tejaswini; Rakam, Niharika; Kadarla, Rohith Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Guillain Barre Syndrome is a peripheral neuropathy that causes acute neuromuscular failure. Guillain, Barré and Strohl used Quinckes method to determine the protein level and cell count in the cerebro spinal fluid of their patients. In 1956, Charles Miller Fisher reported three patient case histories in the New England Journal of Medicine. Guillain-Barré syndrome is rare, incidence worldwide is estimated to be 0.6-4/100,000 person/year and men are about 1.5 times more affected than women. Awareness of these complications, their detection and management may help limit the morbidity of GBS.